Exergames: jogos digitais para longeviver melhor - Nakamura, Ana Lucia (2015)
This bibliographic research aims to identify the exergames contributions in physical, emotional and cognitive aspects. It is based on two main themes: the aging process and the games. The study also identify the elderly preferences about the games and their motivations to play. It describes the aging process and how the elderly use technology, especifically relating to the exergames. The games go beyond the fun when its characteristics are combined with physical exercises. Thus, they can be alternatives for rehabilitation of motor functions, cognitive and improvements in emotional aspects. Through case studies about exergames in reabilitations with Parkinson Disease, Alzheimer, subsyndromic depression, stroke and postural balance, the exergames contributions to the elderly (men and women about 60 to 94 years old from different countries) are shown in this research. This research is based on the games publications of Johan Huizinga, Roger Caillois, Sergio Nesteriuk Gallo, Vicente Mastrcolla and Jenova Chen. The aging process studies are based on publications of Simone de Beauvoir, Beltrina Côrte and Elisabeth F. Mercadante